Looking Beyond the Constitution: Legislative Efforts toward Environmental Rights in Nigeria: A Review of Some Salient Legislations - Umukoro, Brown (Brawijaya Law Journal, 2022)
The search light for environmental rights in Nigeria has been focused on the Constitution of the Federal Republic of Nigeria 1999 (as amended) with occasional references to case laws, which are limited and unprogressive on the subject. Most reviews of relevant legislations on the environment have been centered on themes such as environmental protection, environmental degradation, and damage arising from pollution. Apart from studies on whether the Constitution guarantees any right to clean environment, inquiries are hardly directed at the provisions of other statutes and policies on the environment on the extent to which they support environmental rights. This paper is a review of some salient legislations on environmental protection with a view to establish legislative authority for the right to clean and a healthy and sustainable environment in Nigeria. There exists a notable legislative platform on which one may insist on the right to clean environment in Nigeria notwithstanding the constitutional constraints on the enforcement of the duty of the Government to protect and improve the environment.